Understanding Coping Mechanisms during the COVID-19 Pandemic: a Case Study of Stakeholders of the African Sisters Education Collaborative - Draru, Mary Cecilia (Review of religious research, 2022)
The African Sisters Education Collaborative (ASEC) operates education programs for women religious in ten countries of Africa south of the Sahara. As ASEC prioritizes strong relationships with partner institutions, understanding the impact of the COVID-19 pandemic on these stakeholders is central to providing effective interventions that will ensure continuation of its programs.